Combined treatment by burosumab and a calcimimetic can ameliorate hypophosphatemia due to excessive actions of FGF23 and PTH in adult XLH with tertiary hyperparathyroidism: A case report - Yuichi Takashi; Kyoko Toyokawa; Naoki Oda; Yoshimi Muta; Hisashi Yokomizo; Seiji Fukumoto; Daiji Kawanami (Frontiers in Endocrinology, 2022)
IntroductionX-linked hypophosphatemia (XLH) is the most prevalent type of heritable fibroblast growth factor 23 (FGF23)-related hypophosphatemic rickets. Recently, anti-FGF23 antibody, burosumab, has become clinically available. We herein report a patient with adult XLH and tertiary hyperparathyroidism.Case presentationThe serum phosphate level and tubular maximum reabsorption of phosphate per glomerular filtration rate (TmP/GFR) remained low, despite burosumab treatment. While the influence of the relationship between FGF23 and parathyroid hormone (PTH) on the phosphaturic effect is unclear, it was considered that a high level of PTH due to tertiary hyperparathyroidism remains to suppress renal phosphate reabsorption. A calcimimetic, evocalcet, increased the serum phosphate level and TmP/GFR.Discussion and conclusionTherefore, it is important to evaluate the presence of secondary-tertiary hyperparathyroidism in patients whose serum phosphate level does not increase with burosumab treatment.